Mortality and Embolic Potential of Cardiac Tumors - Dias,Ricardo Ribeiro (2014)
Background: Cardiac tumors are rare, mostly benign with high embolic potential. Objectives: To correlate the histological type of cardiac masses with their embolic potential, implantation site and long term follow up in patients undergoing surgery. Methods: Between January 1986 and December 2011, we retrospectively analyzed 185 consecutive patients who underwent excision of intracardiac mass (119 females, mean age 48±20 years). In 145 patients, the left atrium was the origin site. 72% were asymptomatic and prior embolization was often observed (19.8%). The diagnosis was established by echocardiography, magnetic resonance and histological examination. Results: Most tumors were located in the left side of the heart. Myxoma was the most common (72.6%), followed by fibromas (6.9%), thrombi (6.4%) and sarcomas (6.4%). Ranging from 0.6cm to 15cm (mean 4.6 ± 2.5cm) 37 (19.8%) patients had prior embolization, stroke 10.2%, coronary 4.8%, peripheral 4.3% 5.4% of hospital death, with a predominance of malignant tumors (40% p < 0.0001). The histological type was a predictor of mortality (rhabdomyomas and sarcomas p = 0.002) and embolic event (sarcoma, lipoma and fibroelastoma p = 0.006), but not recurrence. Tumor size, atrial fibrillation, cavity and valve impairment were not associated with the embolic event. During follow-up (mean 80±63 months), there were 2 deaths (1.1%) and two recurrences 1 and 11 years after the operation, to the same cavity. Conclusion: Most tumors were located in the left side of the heart. The histological type was predictor of death and preoperative embolic event, while the implantation site carries no relation with mortality or to embolic event.